Parenting Styles and Family Contributors to the Development of Dietary Behaviors in Arab Children Ages 6-10 Years Old Living in the US - Tami, Suzan; Reed, Debra (International Journal of Child Health and Nutrition, 2020)
Parenting styles and family contributors are the main determinants of obesity risk in children. To date, no research has been reported on parenting styles/practices and family contributors to the development of dietary behaviors in Arab children living in the US. The objectives of this exploratory mixed-method study were to collect data on parenting feeding styles (Caregiver’s Feeding Style Questionnaire- CFSQ) of Arab mothers and family contributors (Family Nutrition Physical Activity- FNPA) to the development of dietary behaviors in their children; and to collect data on Arab mothers' challenges and strategies to promote healthier dietary behaviors in their children. Although all Arab mothers (n=23) self-assessed that they were authoritative, only seven mothers were categorized as having an authoritative feeding style based on their CFSQ scores. The FNPA overall mean was 3.15, indicating less obesogenic family environment and behaviors. Across focus groups, barriers to desirable dietary intake included low vegetable intake and child being distracted by sweets, junk foods, and technology. All mothers wanted their children to have healthier dietary habits and used positive and negative approaches to achieve that. Positive approaches included no pressure to eat and providing healthier alternative foods. Negative approaches included pressuring the child to eat and rewarding with sweets and technology. In correlation analyses, the mother's BMI was significantly correlated with the child's BMI z-scores (r = 0.325, p = 0.005). This study can guide future efforts in assessing parenting style and assessing the home environment regarding the dietary behaviors of Arab families.